Multi-Scale Simulation of Two-Dimensional Chloride Transport Under the Effect of Bending Load in Concrete - Zhang, Lijuan; Zhang, Jianjian; Sun, Guowen; Liu, Zhiyong (Frontiers in Physics, 2021)
The chloride transport in marine concrete under loading is the main cause of its structural deterioration. The traditional numerical simulation assumes that the coefficient of chloride transport is constant, resulting in a large deviation in the prediction results. Based on the porous medium theory, micromechanics theory and the idea of equivalent homogenization, a multi-scale model of the effective diffusion variable coefficient of chloride transport under bending load was established, which was calculated and programmed by the numerical analysis. The results show that the prediction values of the two-dimensional variable coefficient model is basically consistent with the literatures, and the prediction accuracy is significantly improved. In addition, the theoretical simulation proves that the bending load affects the porosity of the cement matrix, and then the diffusion coefficient of chloride is changed in concrete. The compression zone can slow down the chloride transport process, while tension zone will accelerate it. The chloride concentration under tension zone is 42.1% higher than that under compression zone when the diffusion time is 200 d and the concrete depth is 15 mm.